A study on microbiological and chemical changes during the production and storage of potassium sorbate treated and salted carp fillets - Bahri Patır; Ayşe Gürel; Gülsüm Ateş; Ahmet H. Dinçoğlu (Eurasian Journal of Veterinary Sciences)
Microbiological and chemical changes occuired during Ihe production and storage of potassium sorbate treated and salted carp fillets were investigated. The fillets samples wore subjected to sodium chloride with varying radios (5 % and 10 %) and to potassium sorbate with varying ways (by Ireating (he lillets with 0 5 % potassium sorbate and immersing into 5 % potassium sorbate lor 1 mi.). Samples from six different processes including control group were vacuum-packed and slored at 4 ºC. Al certain stages of the production (lillets. end ol sailing and drying) and on days 7. 14. 28 and 56 of storage, the samples were examined microbiologically (total rnesophile aerobe, conform, Staphyloccocus-Micrococcus. Lactobacillus, psychrophlle, yeast and mould) and chemically (moisture. salt, salt in dry matter, pN and TVB-N). Sorbic acid levels were analyzed unlil on day 14 of the storage. Counts of total rnesophile aerobe, colilorm, Staphyloccocus-Micrococcus, Lactobacillus, psychrophile, yeast and mould were decreased with the end ol salting, whereas cohform microorganisms decreased until the end of drying. A! the lollowing stages all the microorganisms were found tc be increased. During the preparation and siorage of ihe produci, the samples treated v/nh 10 % sailed and potassium sorbate were observed lo contain relatively less microorganisms [P > 0.05). Moisture content of 10 % salted samples decreased rapidly (P< 0.05) whereas In 5 % salted samples that remained at higher level and unsimilar variations were detected throughout the storage. Salt levels in all types decreased during production and Storage. However rate of decrease in salt contents of 10 % salted samples were higher (P<0.05) Besides. salt content of 5 % salted samples remained relatively constant until the end of storage (P>0.05). Salt content in dry matter followed Ihe similar path. In all series. pH values diminished fast at (he beginning ol the production whereas Ihe decrease was slow there alier. TVB-N levels in all of the samples remained constant from the beginning of Ihe production until on day 14 of the storage. II increased rapidly reaching the highest level at the end ol ihe siorage there alter Dunng ihe production end storage no significant differences were found between ihe types in terms ol TVB-N levels. Sorbic acid content in samples immersed in to potassium sorbate reached higher levels (P<0.05). ü ıs concluded lhat during the storage of experimentally produced salted carp fillets some chemical parameters moved (n as undesirable course it will be useful to ireat the produci with low consumable properties with in potassium sor-baie and antimicrobial effect ol poiasslm sorbale has increased with Ihe increasing amount ol salt.